EFFICACY OF COSUPPLEMENTATION THERAPY WITH VITAMINS B9, B12, AND D ON ENDOTHELIAL DYSFUNCTION IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Al- Joufi, Fakhria; El- Bana, Mona A; Tewfik, Ihab; Anwar, Mona (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study evaluated the effects of Vitamins D, B9, and B12 given individually or combined in ameliorating some biochemical parameters related to endothelial dysfunction in diabetic rats. Methods: A total of 50 Sprague-Dawley male rats were divided into five groups: Control, diabetic, diabetic received Vitamin D, diabetic received Vitamins B9 and B12, and diabetic received Vitamins B9, B12, and D. At the end of 6 weeks, the rats were sacrificed and a set of assays was carried out to determine: Fasting blood sugar (FBS), lipid profile, nitric oxide (NO), homocysteine (Hcy), malondialdehyde (MDA), and serum levels of Vitamins B9, B12, and D. Results: Diabetic rat received Vitamin D and diabetic rat received Vitamins B9 and B12 had a significant decline in the levels of FBS, lipid profile, and Hcy with reduced MDA (p<0.05) release but significant increase in NO level. On the same hand, diabetic rat received combined supplementation of Vitamins B9, B12, and D had more pronounced effect (p<0.00). Conclusion: Given these findings, the combined vitamins therapy had antiatherosclerotic effects by inhibiting lipid peroxidation and stimulating NO production, resulting in amelioration the endothelial dysfunction in diabetic rat.